(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
A Kenyan philosopher, Henry Odera Oruka (1944–1995), conceptualised and articulated the six trends in African philosophy. These are ethno-philosophy, nationalistic-ideological philosophy, artistic (or literary philosophy), professional philosophy, philosophic sagacity and hermeneutic philosophy. In this article, we maintain that the last three of these trends, namely professional philosophy, philosophic sagacity, and hermeneutic philosophy, are useful in our attempt to contribute to Africanising the school history curriculum (SHC) in the Curriculum Assessment Policy Statement (CAPS) in post-apartheid South Africa. Against this background, we make use of Maton’s (2014) Epistemic-Pedagogic Device (EPD), building on from Bernstein’s (1975) Pedagogic Device as a theoretical framework to view African philosophy and its implications for the Africanisation of the SHC in CAPS in post-apartheid South Africa. rough the lens of Maton’s EPD, we show how the CAPS’ philosophy of education is questionable; untenable since it promotes ‘di erences of content’; and is at the crossroads, i.e., it is stretched and pulled in different directions in schools. Ultimately, we argue that Oruka’s three trends form a three piece suit advertising one’s academic discipline (professional philosophy); showing South Africa’s rich history told in the words of African elders (sage philosophy); and imploring school history learners to embark on a restless, unfinished quest for knowledge in the classrooms in post-apartheid South Africa.